2016
DOI: 10.5665/sleep.6158
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Limb Movements in Sleep are Associated with Greater Cognitive Decline in Older Men without Dementia

Abstract: Study Objectives: To examine the association between periodic limb movements in sleep (PLMS) and change in selected aspects of cognition in community-dwelling older men. Methods: We studied 2,636 older men without dementia who underwent in-home polysomnography with measurement of the periodic limb movement index (PLMI) and periodic limb movement arousal index (PLMAI) using piezoelectric sensors. Random-effects models and logistic regression were used to examine the association between PLMI, PLMAI, and 3-to 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…Because of the decrease in symptom awareness in elderly people, ESS and BSQ scores might have limited use as indicators of sleep disorders [8,24]. Higher values of PLMI have been observed in elderly populations [25,26]; however, the median value of PLMI in our study group was 2.45, and there was no association between PLMI values and increased age.…”
Section: Discussioncontrasting
confidence: 54%
“…Because of the decrease in symptom awareness in elderly people, ESS and BSQ scores might have limited use as indicators of sleep disorders [8,24]. Higher values of PLMI have been observed in elderly populations [25,26]; however, the median value of PLMI in our study group was 2.45, and there was no association between PLMI values and increased age.…”
Section: Discussioncontrasting
confidence: 54%
“…Some studies have suggested an association between PLMS and an increased risk of cardiovascular disorders. 2,14,15 Other studies have demonstrated a correlation between PLMI and affective symptoms and fatigue, 16 cognitive decline (particularly executive function) in older men without dementia, 17 and lower quality of life in children. 18 One study even suggested a possibility of higher mortality in those with PLMI >15/hour.…”
Section: Discussionmentioning
confidence: 98%
“…21 However, our observations should be considered preliminary given sample size limitations. Both apnea-hypopnea index and periodic limb movement index have been associated with decreased cognitive performance [22][23][24] and were also associated with higher BAI.…”
Section: Discussionmentioning
confidence: 99%